Assessment of Seasonal and Spatial Variation of Groundwater Quality in the Coastal Sahel of Doukkala, Morocco - Imane EL Adnani, Abdelkader Younsi, Khalid Ibno Namr, Abderrahim El Achheb and El Mehdi Irzan (Nature Environment and Pollution Technology, 2020)
The current research is set in the context of the impact of climate change at the regional level, particularly focused on seasonal variations and their influence on the physico-chemical characteristics of groundwater in the rural and urban areas of coastal Sahel of Doukkala. The main objective of this study was to evaluate the quality to explain the phenomena at the origin of the mineralization of groundwater. Two measurement campaigns of sampling were carried out on 30 wells, in 2016 and 2018 (dry and wet season). The water points were piezometrically surveyed. In situ, the same water points were measured for temperature, pH, and electrical conductivity, using a multiparameter conductivity meter and a pH meter. The chemical analysis was carried out at the Laboratory of Geosciences and Environmental Technics using volumetry (Ca2+, Mg2+, Cl- and HCO3 -) and spectrophotometry methods (SO4 2-, Na+ and K+); total dissolved solids (TDS) were computed by multiplying the EC by a factor (0.55 to 0.75), depending on relative concentrations of ions. Total hardness (TH) was calculated by taking the differential value between Mg2+ and Ca2+. For the reliability of the results obtained, we proceeded to the application of the ionic balance. The obtained water quality data was subjected to multivariate statistical techniques to evaluate homogeneity and heterogeneity between sampling water and to differentiate water quality variables for temporal variations.The elements are all significantly different among seasons. The dry season was positively associated with EC, TDS, Cl-, Na+, SO4 2- and K+ and negatively associated with temperature, and pH. The wet season was in contrast associated with high values of NO3 - and pH. These results show that the majority of well water in the study area represents strong mineralization that far exceeds standards, especially during the dry period, with an average EC of 416.04 ?S/cm, while the wet season is lower at 382.6 ?S/cm. The hydrochemical classification of water from the Piper diagram revealed only one hydro facies, which is the chlorinated sodium facies. In conclusion, the variability of groundwater quality could be explained by the fact that in the dry season, there is concentration and in the wet season, there is ionic dilution and may also reflect the effect of anthropogenic activity.